Pendampingan Kelompok Tani Desa Sidomukti Kecamatan Kenduruan Kabupaten Tuban: Kajian Partisipatory Action Research (PAR) - M. Ali Mishbah; Ahmad ‘Ainun Najib; Achmad Khoirun Najib; Ahmad Faiz Abdillah; Muhammad Nur Kholis; Muhamad Muhibbuddin Al-Haq; Muhammad Najih; Muhammad Qurtubi; Rizqi Faishol Zain; Abd Rouf; M. Nur Lathif; Masud Safii; A Kurniawan; Akhmad Manan; Moh Husnuddin; Muhammad Abdim Munib; Muhammad Husen; Niswatin Nurul Hidayati; Nurul Novitasari (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of the research and assistance carried out in Sidomukti Village, Kenduruan Sub-District, Tuban District was to make farmers independent for seed sovereignty, production sovereignty, and market sovereignty. The method used was Participatory Action Research. The results obtained are that agriculture is a very crucial field in the lives of Indonesian people. Therefore, the number of innovations and assistance carried out to build or increase agricultural capacity is absolutely necessary. In addition, collaboration between parties will be very helpful in the process of independence in the agricultural sector, both in the fields of seeds, production, and markets. For further researchers and assistants, it is hoped that they can carry out more in-depth research, this is because the research and assistance carried out is only in a fairly short time, so that the implementation evaluation process cannot be carried out optimally. In addition, collaboration from multi stakeholders continues to provide further assistance, especially in collaboration with government agencies, where one of the missions carried out by the current Regent is to increase the added value of the agricultural sector widely, where one of the work programs is one village. one priority, village cooperation, logistical support, and strengthening food security. So that multi-stakeholder cooperation will be established in Sidomukti Village.